Children's disclosures of sexual abuse in a population-based sample. (February 2018) - Lahtinen, Hanna-Mari; Laitila, Aarno; Korkman, Julia; Ellonen, Noora
Abstract: Most previous studies on disclosing child sexual abuse (CSA) have either been retrospective or focused on children who already have disclosed. The present study aimed to explore the overall CSA disclosure rate and factors associated with disclosing to adults in a large population-based sample. A representative sample of 11, 364 sixth and ninth graders participated in the Finnish Child Victim Survey concerning experiences of violence, including CSA. CSA was defined as having sexual experiences with a person at least five years older at the time of the experience. Within this sample, the CSA prevalence was 2.4%. Children reporting CSA experiences also answered questions regarding disclosure, the disclosure recipient, and potential reasons for not disclosing. The results indicate that most of the children (80%) had disclosed to someone, usually a friend (48%). However, only 26% had disclosed to adults, and even fewer had reported their experiences to authorities (12%). The most common reason for non-disclosing was that the experience was not considered serious enough for reporting (41%), and half of the children having CSA experiences did not self-label their experiences as sexual abuse. Relatively few children reported lacking the courage to disclose (14%). Logistic regression analyses showed that the perpetrator's age, the age of the victim at the time of abuse, and having no experiences of emotional abuse by the mother were associated with disclosing to an adult. The results contribute to understanding the factors underlying children's disclosure patterns in a population-based sample and highlight the need for age-appropriate safety education for children and adolescents.